Discussion on “Influence of porosity distribution on free vibration and buckling analysis of multi-directional functionally graded sandwich plates” composite structures, volume 279, 2022, 114795, https://doi.org/10.1016/j.compstruct.2021.114795 - Punera D.; Gopa Chanda A. (My University, 2025)
[No abstract available]